Hyperbolic Discounting and Politics: The beneficial effects of bureaucrats - Marcus Drometer (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2006)
This paper introduces hyperbolic discounting into politics. In our model, politicians act according to the preferences of voters in order to be re-elected. As voters' preferences are dynamically inconsistent, the political process results in an allocation of the public budget that is distorted towards consumption ex- penditures. We show that this inefficiency is mitigated when the influence of bureaucrats who favour an excessive supply of public goods is taken into ac- count. Finally, we derive a positive relationship between the optimal level of a bureaucracy's influence and the relevance of long-term investments in a given policy area.
Keywords: D72; D73; H11; 330; Political Agency; Hyperbolic Discounting; Bureaucracy